Hydrometeorological Variability of Olive Ridley Sea Turtle (Lepidochelys olivacea) Nesting Beaches: Implications for Conservation Practices - Anatoliy Filonov; Enrique Godínez-Domínguez; Iryna Tereshchenko; Cesar O. Monzon; David Avalos-Cueva; María del Refugio Barba-López (Geosciences)
The conservation of the olive ridley turtle (Lepidochelys olivacea) is increasingly critical due to declining global populations. This study investigates the influence of hydrometeorological conditions on the nesting season and annual hatchling sex ratios conducted at the Playón de Mismaloya Federal Reserve in Tomatlán, Jalisco, Mexico. The research specifically examines variations in sand temperature at both the beach surface and nesting depths, with extended measurements taken at multiple depths (20, 40, 60, 80, and 100 cm) to analyze the vertical temperature gradient along the beach. Atmospheric parameters were modeled using Newton’s Cooling Law and solved with the finite difference method to estimate heat loss rates from beach sand to its surroundings, shedding light on microclimatic effects on incubation and embryonic development. Meteorological data were gathered from an automatic weather station, while sand temperatures were monitored with thermographs. During the warm period (approximately 32 °C), sand temperature showed a negative correlation with depth (20–100 cm), indicating cooler temperatures at greater depths. These conditions were associated with female-biased hatchling production. Conversely, the cold period (approximately 28 °C) led to male-biased hatchling production, with a positive correlation between sand and air temperatures. This study emphasizes the importance of monitoring in situ environmental conditions and extending the protection season until February to avoid the loss of male hatchlings.